Estudio de factibilidad para la creación y montaje de un minimarket en el municipio de guaranda sucre (2019)
The development of a business plan for the implementation and assembly of a minimarket in the municipality of Guaranda in the department of Sucre. It aims to provide a different option when it comes to acquiring mass consumption products by the inhabitants of this area, for which a series of investigations have been carried out in order to gather the necessary information to guarantee the viability of the project execution. With the implementation of minimarket it is intended to satisfy the physiological need to feed on customers and their desire to save money and time in making purchases of products. The proposed business will sell mass consumption products, mainly food. Its primary target audience is made up of the homes of the municipality of Guaranda.